Major vascular complications after transfemoral arterial closure system implantation: a single-center study - Chatzigeorgiadis, Pavlos; Hellwig, Konstantin; Almási-Sperling, Veronika; Meyer, Alexander; Lang, Werner; Rother, Ulrich (International Angiology, 2020)
BACKGROUND: During the past decades, the use of vascular closure devices (VCDs) has been established due to the increasing number of interventions. Of particular concern is the perceived risk of VCDs for development of implant-induced vascular major complications. Therefore, the aim of this analysis was to report the variety of vascular access side complications after the use of VCDs, and to analyze the referred risk factors. METHODS: All cases of vascular complications associated with VCD use requiring surgical repair from 2010 to 2016 were retrospectively analyzed in a single center trial. Systemic and local complications, risk factors as pre-existing diseases and their influence on the surgical outcome were evaluated. RESULTS: A total of 46 individuals were included in this study (male/female: 16/30). The total number of interventions in the involved departments of the study center during the same period was 9754 Therefore the complication rate after VCD implantation was 0.47%. The detected complications ranged from symptomatic claudication (N.=24) to acute leg ischemia (N.=19) and major bleeding (N.=3). Surgical reconstruction was performed by direct suture (N.=4), transverse arteriotomy with thrombectomy (N.=2), endarterectomy with patchplasty (N.=35), inguinal graft interposition or bypass (N.=3) and primary major amputation (N.=2). In regard to the risk factors, the study has concluded that atherosclerosis, female gender and diabetes mellitus are correlated with major vascular complications (bleeding and limb ischemia). However, in cases with therapeutic anticoagulation the rate of major bleeding was significantly elevated (P=0.028). CONCLUSIONS: Reported complication rates associated with femoral VCD implantation are low. However, in some cases VCD implantation may account for severe complications including limb losses. Therefore, an adequate patient selection is necessary to detect those cases at higher risk for complications.
CRIS-Team Scopus Importer:2020-04-14